The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/ageing/afy191
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health-related quality of life of care home residents: comparison of self-report with staff proxy responses

Abstract: Introduction care home residents are often unable to complete health-related quality of life questionnaires for themselves because of prevalent cognitive impairment. This study compared care home resident and staff proxy responses for two measures, the EQ-5D-5L and HowRU. Methods a prospective cohort study recruited residents ≥60 years across 24 care homes who were not receiving short stay, respite or terminal care. Resident and staff proxy EQ-5D-5L and HowRu responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Correlations between different measures across different reporters were generally weak to moderate, in line with recent similar studies [11,31]. This suggests that people living with dementia and those who support them do not perceive QoL in the same way, or that they may focus on different aspects of QoL, suggesting a need for several measures to be completed to ensure full coverage of perceived QoL.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Correlations between different measures across different reporters were generally weak to moderate, in line with recent similar studies [11,31]. This suggests that people living with dementia and those who support them do not perceive QoL in the same way, or that they may focus on different aspects of QoL, suggesting a need for several measures to be completed to ensure full coverage of perceived QoL.…”
Section: Discussionsupporting
confidence: 82%
“…It is well established that proxy raters assess QoL lower than self-rated QoL within dementia research [8], since these two groups may have different concepts of QoL [9]. Correlation between scores on QoL measures specifically designed for people with dementia are generally low-to-moderate between self-, staff-proxy and relative-proxy, suggesting poor agreement [10,11] and it is unclear who is the more accurate reporter [12]. The difference between proxy-and self-rated QoL is greater for individuals with higher levels of impaired cognition [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In China Guidelines for Pharmacoeconomic Evaluations, one of the most important HTA guidelines in China, EQ-5D is one of the four recommended preferred outcome for QoL [15]. To date, extensive studies have assessed the inter-rater reliability between self-report and proxy-report EQ-5D [16][17][18][19][20][21][22][23][24][25][26][27][28]. The inter-rater reliability is primarily measured using precision-the strength of agreement between proxy and patient responses, and bias-systematic difference in proxy response [29].…”
Section: Introductionmentioning
confidence: 99%
“…The inter-rater reliability is primarily measured using precision-the strength of agreement between proxy and patient responses, and bias-systematic difference in proxy response [29]. These existing studies primarily investigated the inter-rater reliability on specific population, such as children [19,27], older adults [24,27,28], dementia [16,18,21,[23][24][25], stroke [17], prolonged mechanical ventilation [20], intensive care [22], and vascular cognitive impairment [25]. In general, most of these studies showed that proxies were inclined to under-estimate the patients' health conditions, and proxy-reports and patient-reports did not agree and were inconsistent in terms of proxy type (e.g.…”
Section: Introductionmentioning
confidence: 99%